TOPICAL ISSUES OF BRINGING A SPECIAL CATEGORY OF PERSONS TO CRIMINAL RESPONSIBILITY UNDER THE CRIMINAL PROCEDURE LEGISLATION OF THE REPUBLIC OF ARMENIA - Avetisyan, Serjik (State and Law, 2021)
The article discusses the controversial issues of bringing a special category of persons to criminal responsibility under the current and adopted new Criminal Procedure Code of the Republic of Armenia (hereinafter – the RA Code of Criminal Procedure); identifies existing gaps in legislation; analyzes judicial practice, as well as the legal positions of the Constitutional Courts of the Republic of Armenia and the Russian Federation; suggests ways to improve legislation, as well as practical recommendations for the application of relevant criminal procedure norms.
Keywords: criminal procedure form; special subject; immunity; criminal prosecution; deprivation of immunity